Aperture polarimetry of selected comets in 2018–2020: Observations and computer simulation. (November 2022) - Zhuzhulina, E.; Petrov, D.; Kiselev, N.; Karpov, N.; Savushkin, A.
Highlights: Polarimetric observations of 19 comets (9 short-period and 10 for long-period) were carried out in the V, R, I bands. Phase curves of linear polarization degree are constructed over a wide range of phase angles. Computer simulations of the polarization curves of the silicate-carbon mixture were carried out. For the interpretation of observational data multispectral observations in at least 3 different spectral ranges are required. For a reliable interpretation of observations, the model particles with internal porosity should be used. Abstract: Polarimetric studies are an important source of information about the physical properties of celestial bodies. In 2018, we put into operation the new two-channel polarimeters in the Crimean Astrophysical Observatory and the Peak Terskol Observatory. With the help of these instruments, in the period from 2018 to 2020, we carried out measurements of the polarization characteristics of 19 comets. Based on these data, we obtained the phase dependences of linear polarization degree of comets in the R, V, and I broadband filters. We approximate the polarization curves by a trigonometric expression. It was found that in the region of negative polarization, the phase curves of polarization in all three filters practically coincide. We also found that there is a noticeable difference in the degree of linear polarization between short-period and long-period comets. The polarization minimum of short-period comets is almost twice as high as that of long-period comets. It is shown, that for the interpretation of observational data, multispectral observations in at least three different spectral ranges are required. Moreover, for a reliable interpretation of observations, model particles with internal porosity should be used.